Expanding the immunotherapy universe in extensive-stage small cell lung cancer: from chemoimmunotherapy backbone to next-wave combinations - Chi, Xiang; Dong, Yan; Zhu, Lide; Su, Di; Wu, Haolin (Frontiers in Immunology, 2025)
Small-cell lung cancer (SCLC) is a highly malignant neuroendocrine tumor characterized by rapid proliferation and dismal prognosis. Platinum-based chemotherapy combined with immune checkpoint inhibitors (ICIs) is now the first-line treatment for extensive-stage disease (ES-SCLC), extending the overall survival (OS) period of these patients by 2–5 months, yet durable remissions remain the privilege of fewer than 20% of patients. Despite intensive investigation, this incremental benefit appears to have plateaued, prompting exploration of alternative combination strategies to unleash deeper and more durable antitumor synergy. Recent phase II/III trials integrating anti-angiogenic agents into the chemo-immunotherapy have reported unprecedented OS gains of up to 7 months, redefining therapeutic expectations. Concurrently, chemoradiation with ICIs triplet regimens have demonstrated encouraging antitumor activity in ES-SCLC, while rational combinations of small-molecule targeted drugs (DLL3 inhibitors, PARP inhibitors) combined with ICIs or epigenetic modifiers with ICIs are yielding early signals of efficacy. Nevertheless, primary resistance, absence of robust predictive biomarkers, and cumulative toxicity continue to curtail clinical impact. This Review provides a comprehensive, evidence-based map of the evolving ES-SCLC immunotherapy combination landscape. We critically dissect competing therapeutic paradigms, juxtapose corroborative and contradictory data, and distill actionable insights for future trial design, biomarker development, and regulatory strategy.